Status and prospects of financial support of research activities of higher education institutions Ministry of Education and Science in cooperation with the International Centre for Scientific and Technical Information - A. A. Lebedev; E. V. Ugrinovich (Informaciâ i Innovacii)
The article analyzes the state and prospects of financial support for research activities of universities subordinate to the Ministry of education and science of Russia in the framework of cooperation with the International center for scientific and technical information. The article examines the financial contribution of each ICSTI member country to the research activities of higher education institutions of the Ministry of education and science of Russia for the period 2013 – 2017. The author defines the main stable directions and trends of financial support of higher education institutions of the Ministry of education and science of Russia in the field of scientific and technical cooperation with the ICSTI member countries. The author has established a ranking and identified groups of ICSTI member countries that have the greatest impact on the financial support of research activities of higher education institutions of the Ministry of education and science of Russia. The author has developed proposals on the prospects of financial support for research activities of universities subordinate to the Ministry of education and science of Russia.